(untitled) (Research, Society and Development, 2023)
Introduction: The discussion between the existence or not of influence of obesity on the incidence of bone fractures raises an extremely relevant physiological clash in the endocrine and orthopedic scenario, and it is essential to deepen this medical correlation. Objective: The present study aimed to evaluate the clinical and epidemiological aspects, and the correlation between obesity and bone fractures in general. Materials and Methods: This is an integrative literature review of the physiological aspects of bone tissue and the pathophysiological aspects of obesity, seeking to obtain a correlation between them in the context of bone fractures. The PICO strategy was used to prepare the guiding question. Furthermore, the descriptors “Obesity” were crossed; “Bone Fractures”; “Complications”, in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO), Ebscohost, Google Scholar and Virtual Health Library (BVS) databases. Results and Discussion: A significant portion of the articles demonstrated that there is a correlation between bone fractures and obesity, although its protective role, which was established, is currently questioned. Conclusion: It was possible to perceive that there are points of metabolic convergence between the pathophysiology of obesity and the physiology of bone tissue, highlighting the theoretical possibility of greater bone fragility in obese patients.